RUANG PEMBERDAYAAN DAN EKSPLORASI POTENSI AIR DI WADUK TOMANG - Yoga Gouwijaya; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2021)
At the author’s self-authentication stage during the COVID-19 pandemic, looking at perspective of water in Jakarta that has been capitalized and controlled by the fresh water scarcity campaign. The perspective of water divided into fresh water and polluted water, that raises resident’s concerns about living in utilizing water. This makes the vital programs in large water reservoirs, such as Tomang Reservoir, that can be a place to properly empower the district, the integration between humans and water brings out the potential of this water. With the experimental architecture method and Bio-Integrated Design, spatial narrative in Tomang Reservoir presents space and visual that created by the water of Tomang Reservoir, and can provide benefits for humans and the environment, starts from the desire to save, accept, waiting, and start to realize moments, ideas, or new things to get to dwelling, so that the programs that formed can recover the environment and human’s survival. Not only to produce architectural buildings, but also non-architectural, and the result can be widely disseminated and trigger the enthusiasm for the residents in other places to process and utilize water. This project that redefining water can present a cultural element in responding to water between fresh water and polluted water, and the results can also be enjoyed by the wider community. This also answers the challenges of The Future of Dwelling itself. Keywords: Culture; Dwelling; Reimagining Water; Water DimensionAbstrakPada tahap otentikasi diri penulis selama pandemi ‘Covid-19’, melihat gambaran gambaran tentang air di Jakarta yang telah di kapitalisasi dan dikendalikan oleh kampanye kelangkaan air bersih. Pandangan mengenai air terbagi menjadi air bersih dan air kotor memunculkan kekhawatiran masyarakat dalam berhuni dalam memanfaatkan air. Hal ini membuat adanya program vital pada tempat penampungan air besar seperti Waduk Tomang dapat menjadi wadah untuk memberdayakan kawasan dengan baik, integrasi antara manusia dan air memunculkan potensi dari air tersebut, Dengan metode arsitektur eksperimental yang didukung dengan Bio-Integrated Design, narasi spasialitas di Waduk Tomang menghadirkan ruang dan visual hasil cipta atau produk dari ‘air’ Waduk Tomang yang dapat memberikan keuntungan bagi manusia dan lingkungan. Dimulai dari keinginan menyelamatkan, menerima, menunggu dan memulai merealisasikan momen, ide, atau hal yang baru untuk menuju dwelling. Sehingga program yang terbentuk dapat memperbaiki lingkungan serta keberlangsungan hidup manusia. Tidak hanya menghasilkan banguna arsitektural tetapi juga produk air kreatif non-arsitektural, hasilnya dapat disebarkan secara luas dan memicu semangat masyarakat di tempat lain dalam mengolah dan memanfaatkan air. Sehingga dapat dikatakan dari proyek memaknai kembali air dapat menghadirkan unsur budaya dalam menanggapi air antara air bersih dan kotor yang hasilnya juga dapat dinikmati oleh masyarakat luas. Hal ini juga menjawab tantangan dari The Future of Dwelling itu sendiri.